PENGAWASAN DAN PEMBINAAN MAHKAMAH AGUNG TERHADAP PENGADILAN DI BAWAHNYA - Fadlil Sumadi, Ahmad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The independence and impartiality of the judicial authority, in the history of its incorporation into norms, had undergone some improvements and impediments along with the changes in the 1945 Constitution of the Republic of Indonesia, which was subsequently followed by amandment in the judicial power. In general, the changes were intended as an effort to reinforce the implementation of the judicial power. The research aimed at studying the design of the regulation concerning the supervision and guidance by the Supreme Court to the lower courts from the perspective of the principles of democracy. The supervision and guidance in the respect were limited to those within the functions and organization of human resource management. The study is a normative legal one using doctrinal method to analyze the laws constructed by the legislative power and thus is apart from the constitutional and political choices at that time. The research had found several designs of laws in the court supervision and guidance. Constitutionally, it had been determined that the Supreme Court should perform the internal supervision while the Judicial Commision, perform the external one. In addition, the law had determined that the supervision should not reduce the independence and impartiality of the judge. Together, the Supreme Court and the Judicial Commision composed the Code of Ethics and Code of Conduct as tools of measurement.